4CPS-263 Case report of Kawasaki disease and SARS-CoV-2 infection in a paediatric hospital. (14th March 2021) - Murrja, E; Simonini, A; Ortenzi, GB; Sentinelli, R; Garzone, AMF; Andresciani, E; Pelliccioni, S; Pompilio, A
Abstract : Background and importance: Kawasaki disease (KD) is a systemic vasculitis of unknown aetiology that affects children younger than 5 years old. The SARS-CoV-2 COVID pandemic highlighted cases reported to have an association between SARS-CoV-2 infection and KD. Clinical analogies verified between the two conditions open new perspectives with regard to aetiopathogenesis. Aim and objectives: To describe a severe hyperinflammation case of a 9-year-old girl (27 kg, 131 cm), previously healthy (mother tested positive for SARS-CoV-2; symptoms of high fever, diarrhoea, headache, abdominal pain), with clinical data regarding the association of SARS-CoV-2 infection and KD. Material and methods: In collaboration with the clinician, we reviewed a medical chart of a KD SARS-CoV-2 associated case, diagnosed between January and July 2020. Results: On 16 April 2020, a 9-year-old girl was admitted to the emergency department for suspicion of acute abdomen with an associated persistent fever. Nasopharyngeal swab and bronchoalveolar lavage tests for SARS-CoV-2 were negative. Abdominal ECO showed lymphadenomegaly due to hyperinflammation and CT scan reported evidence of interstitial, parenchymal thickening and pulmonary infiltration. Echocardiogram showed normal coronary arteries with minimal pericardial effusion. Broad spectrum empirical antibiotics were started. On 18 April (illness day 7) respiratory distress appeared, a critical condition similar to a shock syndrome and multiorgan failure occurred. Respiratory support and ionotropic agents were started in the intensive care unit. The diagnostic suspicion of atypical incomplete KD, non-coronary involvement, was confirmed and treatment was switched to intravenous immunoglobulin 2 g/kg/day, acetylsalicylic acid 30 mg/kg/day and methylprednisolone infusion until the day of discharge. On illness day 10, laboratory blood tests showed progressive reduction in inflammation markers and rapid normalisation of liver enzymes (lipase 1824, amylase 502, declining leucocytes 8.57, Hb 12, negative CRP). Because of the uncertainty about the cause, anti-S-specific IgG antibodies to SARS-CoV-2 were measured. Serology testing for SARS-Cov-2 revealed IgG antibody concentrations. On day 12 of the illness, she was discharged. Conclusion and relevance: It is known that SARS-CoV-2 infection can activate uncontrolled inflammation. Cases are being informally reported among paediatricians, and recently patients with severe forms have been reported, emphasising the apparent rise in the number of children presenting with a multisystem inflammatory state requiring intensive care. The connection between viral infections and KD, the analogies between the two conditions, open new perspectives with regard to aetiopathogenesis. References and/or acknowledgements: Conflict of interest: No conflict of interest